A novel nanostructured composite formed by interaction of copper octa(3-aminopropyl)octasilsesquioxane with azide ligands: Preparation, characterization and a voltammetric application - do Carmo, Devaney Ribeiro [UNESP]; Paim, Leonardo Lataro [UNESP]; Metzker, Gustavo; Dias Filho, Newton Luiz [UNESP]; Stradiotto, Nelson Ramos [UNESP] (Pergamon-Elsevier B.V. Ltd, 2010)
This study presents the preparation, characterization and application of copper octa(3-aminopropyl)octasilsesquioxane following its subsequent reaction with azide ions (ASCA). The precursor (AC) and the novel compound (ASCA) were characterized by Fourier transform infrared spectra (FTIR), nuclear magnetic resonance (NMR), electron paramagnetic resonance (EPR), scanning electronic microscopy (SEM), X-ray diffraction (XRD), Thermogravimetric analyses and voltammetric technique. The cyclic voltammogram of the modified graphite paste electrode with ASCA (GPE-ASCA), showed one redox couple with formal potential (E(1/2)(ox)) = 0.30 V and an irreversible process at 1.1 V (vs. Ag/AgCl; NaCl 1.0 M; v = 20 mV s(-1)). The material is very sensitive to nitrite concentrations. The modified graphite paste electrode (GPE-ASCA) gives a linear range from 1.0 x 10(-4) to 4.0 x 10(-3) mol L(-1) for the determination of nitrite, with a detection limit of 2.1 x 10(-4) mol L(-1) and the amperometric sensitivity of 8.04 mA/mol L(-1). (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Nanostructures; Composites; Chemical synthesis; Electrochemical properties; Electrochemical measurements